1981
DOI: 10.1083/jcb.89.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Role of nuclear glycogen synthase and cytoplasmic UDP glucose pyrophosphorylase in the biosynthesis of nuclear glycogen in HD33 Ehrlich-Lettré ascites tumor cells.

Abstract: Biochemical and autoradiographic evidence show both glycogen synthesis and the presence of glycogen synthase (UDP glucose [UDPG] : glycogen 4-a-D-glucosyltransf erase; EC 2.4 .1 .11) in isolated nuclei of Ehrlich-Lettre mouse ascites tumor cells of the mutant subline H D33. 5 d after tumor transplantation, glycogen (average 5-7 pg/cell) is stored mainly in the cell nuclei . The activity of glycogen synthase in isolated nuclei is 14 .5 mU/mg protein. At least half of the total cellular glycogen synthase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…It is reasonable to assume that glycogen-containing nuclei of pituicytes have the enzymes of glycogen synthesis, which must enter the nucleus by diffusion from the cytoplasm. This is consistent with the biochemical and autoradiographic evidence (Zimmermann et al, 1976a;Granzow et al, 1981) of glycogen synthesis and the presence of glycogen synthase in nuclei of Ehrlich ascites cells. Although the presence of intranuclear glycogen in pituicytes is exceptional, it probably reflects the metabolic plasticity of these cells which, under certain metabolic conditions, allows the translocation of enzymes of glycogen synthesis from the cytoplasm into the nucleus.…”
Section: Discussionsupporting
confidence: 91%
“…It is reasonable to assume that glycogen-containing nuclei of pituicytes have the enzymes of glycogen synthesis, which must enter the nucleus by diffusion from the cytoplasm. This is consistent with the biochemical and autoradiographic evidence (Zimmermann et al, 1976a;Granzow et al, 1981) of glycogen synthesis and the presence of glycogen synthase in nuclei of Ehrlich ascites cells. Although the presence of intranuclear glycogen in pituicytes is exceptional, it probably reflects the metabolic plasticity of these cells which, under certain metabolic conditions, allows the translocation of enzymes of glycogen synthesis from the cytoplasm into the nucleus.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, a number of studies have reported glycogen in association with the nuclear envelope, the endoplasmic reticulum, and the annulate lamellae of embryonic and transformed cells [14,[39][40][41]. Glycogen has also been reported inside the nucleus [42][43][44][45][46]. Moreover, glycogen consistently appears in the Xenopus embryo during the cleavage stage [47].…”
Section: Discussionmentioning
confidence: 94%
“…A number of studies have reported glycogen in association with the nuclear envelope, the endoplasmic reticulum, and with annulate lamellae of embryonic and transformed cells (Coimbra and Lebland, 1966;Flaks, 1968;Eyal-Giladi et al, 1985;Kessel, 1989;Hubbard et al, 1990;Kessel and Beams, 1990). Glycogen has also been reported inside the nucleus (Himes and Pollister, 1962;Karasaki, 1971;Mori et al, 1970;Granzow et al, 1981;Kopun et al, 1989; for a review of intranuclear glycogen see Ferrans et al, 1975). These reports of glycogen in close apposition with nuclear envelopes and annulate lamellae may represent a structural association, or merely a circumstantial association.…”
Section: Models For Glycogen Activitymentioning
confidence: 98%